Research on Microstructure and Performance of Starch/Poly(Vinyl Alcohol) Composites under Volumetric Elongational Deformation - Zhou, Xiling; Jiang, Haowei; Zhang, Yingpei; Zhang, Senhao; Li, Jianjun; Feng, Yanhong; Qu, Jinping (Industrial & engineering chemistry research, 2025)
Although poly(vinyl alcohol) (PVA) is commonly used to reinforce starch-based materials, the significant difference in melting behavior between starch and PVA makes it difficult to simultaneously achieve effective plasticization of PVA and preservation of high molecular weight starch during conventional melt processing. Even with plasticizers, traditional methods often result in molecular degradation and phase incompatibility, which limits the final performance. In this study, we employed a novel biaxial eccentric rotor extruder (BERE) for plasticization and transportation, dominated by volumetric elongational flow, which minimizes shear-induced degradation and facilitates PVA plasticization through periodic compression and release. This process improves the interfacial compatibility between starch and PVA. Morphological and structural characterizations confirm the formation of a cocontinuous phase morphology in blends with a starch content of 60–90%. The composites prepared via BERE exhibit reduced crystallinity, higher molecular weight retention, and enhanced mechanical strength compared with those prepared using conventional twin-screw extrusion. This work demonstrates the potential of elongational flow processing in fabricating high-performance biodegradable starch/PVA composites without the need for chemical compatibilizers.